Production efficiency of beef cows with different milk yield potentials - Filho, Kepler Euclides; de Figueiredo, Geraldo Ramos; Euclides, Valéria Pacheco Batista (Pesquisa Agropecuaria Brasileira, 1995)
The data for this study were collected from 246 animals born in the years 1990 and 1991. These animals were progenies of F1 cows sired by Fleckvieh, Charolais and Chianina bulls mated with Nellore cows. The main objective was to evaluate cows with different milk yield potentials with respect to efficiency of production. The results obtained allow the conclusion that there were differences (P < 0.05) among the cow genetic groups for birth weight, weaning weight and weaning efficiency measured as kilograms of calf weaning weight by kilograms of cow weight at the weaning of her calf. Sex of the calf also affected (P < 0.05) all three traits studied, with the male calves being superiors for all of them. The best efficiency at weaning was recorded for the Fleckvieh-Nellore F1 cows. There was no difference (P > 0.05) between the Chianina-Nellore and the Charolais-Nellore F1 cows.
Keywords: efficiency at weaning; crossbred cows; beef cattle